Joint Hypermobility Is a Risk Factor for Musculoskeletal Pain During Adolescence: Findings of a Prospective Cohort Study. Issue 4 (28th March 2013) - Tobias, Jonathan H.; Deere, Kevin; Palmer, Shea; Clark, Emma M.; Clinch, Jacqui
Abstract: Objective: To determine whether joint hypermobility (JH) in childhood is a risk factor for the subsequent development of musculoskeletal pain. Methods: JH was determined according to the Beighton score at age 13.8 years in children from the Avon Longitudinal Study of Parents and Children (ALSPAC), using a cutoff of ≥6 for the presence of hypermobility. Musculoskeletal pain was evaluated by questionnaire at age 17.8 years. Logistic regression analysis was performed in 2, 901 participants (1, 267 boys and 1, 634 girls) who had complete data. Results: A total of 4.6% of participants had JH at age 13.8 years. Moderately troublesome musculoskeletal pain at age 17.8 years was reported most commonly in the lower back (16.1%), shoulder (9.5%), upper back (8.9%), knee (8.8%), neck (8.6%), and ankle/foot (6.8%). JH was associated with an increased risk of at least moderately troublesome musculoskeletal pain at the shoulder (odds ratio [OR] 1.68 [95% confidence interval (95% CI) 1.04, 2.72]), knee (OR 1.83 [95% CI 1.10, 3.02]), and ankle/foot (OR 1.82 [95% CI 1.05, 3.16]) (adjusted for sex, maternal education, and body mass index). An equivalent relationship was not observed at other sites, including the spine, elbows, hands, and hips. In analyses examining interactions with obesity, associations between JH and knee pain showed higher ORs in obese participants (OR 11.01) as compared with nonobese participants (OR 1.57) ( P = 0.037 for the interaction of hypermobility and obesity). Conclusion: JH represents a risk factor for musculoskeletal pain during adolescence, comprising a specific distribution, namely, the shoulder, knee, and ankle/foot. These relationships were strongest in the presence of obesity, which is consistent with a causal pathway whereby JH leads to pain at sites exposed to the greatest mechanical forces.